2011
DOI: 10.3109/01913123.2011.574249
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Organ Invasion by Viruses: Pathological Characteristics in Three Fatal Cases of the 2009 Pandemic Influenza A/H1N1

Abstract: To further understand the pathological characteristics of multiple organ involvement of the 2009 pandemic influenza A/H1N1 infection, tissues of bronchial mucosa, lung, myocardium, gastrocnemius, and liver from 3 patients with fatal A/H1N1 infections were investigated by light microscopy and transmission electron microscopy. In all 3 patients, bronchial mucosa showed necrotizing bronchiolitis, epithelial necrosis and desquamation, and squamous metaplasia, while lung consolidation or fibrosis was identified. My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Efficient dissemination of F virus might have contributed also to increase the severity of the infection. Accordingly, viral particles have been found in the hearts of both domestic ducks infected with H5N1 highly pathogenic avian virus [55] and fatal cases of 2009 pandemic infected patients [56]. Extrapulmonary complications of influenza virus infection have been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient dissemination of F virus might have contributed also to increase the severity of the infection. Accordingly, viral particles have been found in the hearts of both domestic ducks infected with H5N1 highly pathogenic avian virus [55] and fatal cases of 2009 pandemic infected patients [56]. Extrapulmonary complications of influenza virus infection have been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the direct infection and lysis of muscle cells [1,49] is supported by the isolation of influenza viruses from IAM patients’ skeletal muscle samples, or the observation of viral particles in muscle tissue [30-33,35,39,40]. Extra-pulmonary replication of influenza viruses is rarely reported in infected individuals, but viremia is sometimes detected even in patients with mild disease and was found in pandemic influenza A (H1N1) patients with acute illness and with elevated CK levels [49].…”
Section: Discussionmentioning
confidence: 99%
“…In one case, viral particles and viral antigens in muscle cells were also detected in situ [30]. More recently, three fatal cases of pneumonia due to the new influenza A H1N1 pandemic virus showed multiple organ invasion with viral particles being detected in the skeletal muscle [40]. …”
Section: Introductionmentioning
confidence: 99%
“…198,199 Post-mortem study of three fatal cases of A(H1N1)pdm09 virus infection demonstrated viral particles in the endothelial cells, sinusoidal epithelial cells, and hepatic macrophages. 200 Influenza virus has also been isolated and cultured from the liver of a patient that died of influenza A infection. 201 immediately following infection and demonstrated a delayed response to corticosteroids.…”
Section: Hepatic Complications Of Influenzamentioning
confidence: 99%